2022
DOI: 10.3390/app12136779
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Metabolite Production in High-Altitude Microalgal Strains by Optimized C/N/P Ratio

Abstract: This study evaluated the role of C/N/P in the increase in the synthesis of carbohydrates, proteins, and lipids in two high-mountain strains of algae (Chlorella sp. UFPS019 and Desmodesmus sp. UFPS021). Three carbon sources (sodium acetate, sodium carbonate, and sodium bicarbonate), and the sources of nitrogen (NaNO3) and phosphate (KH2PO4 and K2HPO4) were analyzed using a surface response (3 factors, 2 levels). In Chlorella sp. UFPS019, the optimal conditions to enhance the synthesis of carbohydrates were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 147 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…It is suggested that different PSY genes family is responsible for microalgae development and cell defense under environmental stress [3,16]. Also, the composition and combination of nutrient content in the medium (C:N:P ratio) can affect the content of carotenoids in microalgae [17].…”
Section: Carotenoid Biosynthesis In Microalgaementioning
confidence: 99%
“…It is suggested that different PSY genes family is responsible for microalgae development and cell defense under environmental stress [3,16]. Also, the composition and combination of nutrient content in the medium (C:N:P ratio) can affect the content of carotenoids in microalgae [17].…”
Section: Carotenoid Biosynthesis In Microalgaementioning
confidence: 99%
“…The production of marine-based nanoparticles from a variety of sources, including bacteria, fungus, seaweeds, and marine plants, has received considerable attention [ 33 ]. Algae with high cell growth rates, high stress tolerance, and an abundance of physiologically active substances, such as Ulva lactuca , Spirulina platensis , and Sargassum muticum , are regarded as promising biocatalysts for the synthesis of various types of nanomaterials [ 40 , 41 , 42 ]. Among pure algal compounds, phloroglucinol, eckol, phlorofucofuroeckol A, fucodiphlorethol G, 7-phloroeckol, 6,6′-bieckol, and dieckol act as effective reducing agents in the nanoparticle synthesis process [ 43 ].…”
Section: Marine Organisms and Compounds For The Green Synthesis Of Npsmentioning
confidence: 99%